2022
DOI: 10.3389/fcimb.2021.815627
|View full text |Cite
|
Sign up to set email alerts
|

Probing Immune-Mediated Clearance of Acute Middle Ear Infection in Mice

Abstract: Acute otitis media (AOM) is commonly caused by bacterial pathobionts of the nasopharynx that ascend the Eustachian tube to cause disease in the middle ears. To model and study the various complexities of AOM, common human otopathogens are injected directly into the middle ear bullae of rodents or are delivered with viral co-infections which contribute to the access to the middle ears in complex and partially understood ways. Here, we present the novel observation that Bordetella bronchiseptica, a well-characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…and no bacteria were recovered from the MEs by day 56 p.i., indicating complete clearance. Histological examination of HE stained sections from previous studies (Dewan et al, 2022) showed evidence of inflammation and hypercellularity at day 7 p.i (peak of infection) (Figure 1B). Here we find that by day 56 inflammation had subsided.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…and no bacteria were recovered from the MEs by day 56 p.i., indicating complete clearance. Histological examination of HE stained sections from previous studies (Dewan et al, 2022) showed evidence of inflammation and hypercellularity at day 7 p.i (peak of infection) (Figure 1B). Here we find that by day 56 inflammation had subsided.…”
Section: Resultsmentioning
confidence: 72%
“…We next turned our attention to examining the contributions of humoral and cellular components of adaptive immunity on convalescent protection. We had previously observed (Dewan et al, 2022) that when immune serum collected from convalescent WT mice (day 56 p.i.) was intraperitoneally injected into naive Rag-1 -/mice and challenged, bacterial CFUs in the MEs were reduced by ~100-fold compared to untreated Rag-1 -/mice.…”
Section: Immune Cells From the Spleens Traffic To The Middle Earsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice infected with B. bronchiseptica experienced a steep decline (>95% reduction) in bacterial numbers between 7 and 14 dpi. This decline continued to 56 dpi, and B. bronchiseptica was cleared from the middle ears by 100 dpi ( Dewan et al, 2022 ) by the generation of a robust adaptive immune response ( Dewan et al, 2022 ). In contrast, B. pseudohinzii persisted in the middle ears at high numbers, approximately 10,000 CFU, until at least day 100, the end of this timecourse, with no apparent decline, suggesting infection is chronic, potentially life-long ( Figure 1 and data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its strengths as a model for OM, B. pseudohinzii has also been investigated as an upper respiratory tract pathogen that forms biofilms ( Clark et al., 2016 ) and is cytotoxic to ciliated epithelial cells ( Perniss et al., 2018 ). In contrast to B. pseudohinzii , a related species, B. bronchiseptica , can highly efficiently colonize both nasal cavity and middle ears of mice, and persists for life in the noses but is cleared from the middle ears by processes that involve adaptive immunity ( Dewan et al., 2019 ; Dewan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%